2021
DOI: 10.7554/elife.69909
|View full text |Cite
|
Sign up to set email alerts
|

Dysfunctions of the paraventricular hypothalamic nucleus induce hypersomnia in mice

Abstract: Hypersomnolence disorder (HD) is characterized by excessive sleep, which is a common sequela following stroke, infection, or tumorigenesis. HD is traditionally thought to be associated with lesions of wake-promoting nuclei. However, lesions of a single wake-promoting nucleus, or even two simultaneously, did not exert serious HD. Therefore, the specific nucleus and neural circuitry for HD remain unknown. Here, we observed that the paraventricular nucleus of the hypothalamus (PVH) exhibited higher c-fos expressi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
52
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(55 citation statements)
references
References 65 publications
3
52
0
Order By: Relevance
“…Over 90% of PVH CRH neurons express vglut2 mRNA (Ziegler et al, 2005). Studies show that both the PVN CRH neurons and PVN vglut2 neurons could regulate arousal behavior (Ono et al, 2020;C. R. Chen, et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Over 90% of PVH CRH neurons express vglut2 mRNA (Ziegler et al, 2005). Studies show that both the PVN CRH neurons and PVN vglut2 neurons could regulate arousal behavior (Ono et al, 2020;C. R. Chen, et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Patients with PD, AD, Kleine-Levin Syndrome, and idiopathic hypersomnia, in which LH orexinergic and PB glutamatergic neurons are thought to function normally, still show hypersomnolence ( Bollu et al, 2018 ). Furthermore, dysfunctions of the PVH induced hypersomnia-like behaviors in mice ( Chen et al, 2021 ) and patients with narcolepsy type 1 showed reduced numbers of corticotropin-releasing hormone neurons in the PVH ( Shan et al, 2022 ), further supporting the importance of the PVH in arousal controlling and maintenance. Therefore, our case report first provides clinical evidence that dysfunctions of the PVH area led to hypersomnia in patients.…”
Section: Discussionmentioning
confidence: 92%
“…Other studies have found that the presence of autoreactive CD8 + and CD4 + T cells in narcolepsy, providing further support to the pivotal role of specific T cells in causing neuronal damage in human narcolepsy ( Adamantidis et al, 2007 ; Yokota et al, 2015 ). Besides, some studies reported the association between AQP4-IgG, MOG antibodies and hypersomnia ( Kaur et al, 2013 ; Bollu et al, 2018 ; Chen et al, 2021 ) or disorder associated with MOG antibodies and hypersomnia ( Liu et al, 2020 ), with regression of hypersomnia after appropriate treatment of the autoimmune disease. On the other hand, it has been recently shown that an up-regulation of anti-MOG antibodies can be modulated by prolactin ( Shan et al, 2022 ), a hormone correlated with the onset of hypersomnia ( Kume et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…The dorsomedial hypothalamus (DMH) is a brain region adjacent to the third ventricle and located caudal and ventral to the paraventricular nucleus of the hypothalamus, which is critical for arousal promotion and maintenance [4], food intake, and locomotor activity [5]. The lateral portion of the DMH is adjacent to both the fornix and the lateral hypothalamic area [6], which is a heterogeneous nucleus [7] associated with sleep-wake regulation [8], feeding behavior, and energy metabolism [9].…”
Section: Introductionmentioning
confidence: 99%